2005
DOI: 10.1038/sj.embor.7400334
|View full text |Cite
|
Sign up to set email alerts
|

CTCF is conserved from Drosophila to humans and confers enhancer blocking of the Fab‐8 insulator

Abstract: Eukaryotic transcriptional regulation often involves regulatory elements separated from the cognate genes by long distances, whereas appropriately positioned insulator or enhancer-blocking elements shield promoters from illegitimate enhancer action. Four proteins have been identified in Drosophila mediating enhancer blocking-Su(Hw), Zw5, BEAF32 and GAGA factor. In vertebrates, the single protein CTCF, with 11 highly conserved zinc fingers, confers enhancer blocking in all known chromatin insulators. Here, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
253
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 223 publications
(267 citation statements)
references
References 30 publications
10
253
0
4
Order By: Relevance
“…First, CTCF-binding sites should exist between individual genes of a Hox cluster. This property is well documented in both vertebrates and Drosophila (10,28,40,43,55,56), suggesting that it existed in the ancestor of protostomes and deuterostomes. Second, owing to the stability of the proposed kernel, one should find signs of conservation at least at some CTCF-binding sites.…”
Section: Conservation Of Ctcf Sites In Vertebrate and Drosophila Hox mentioning
confidence: 95%
See 2 more Smart Citations
“…First, CTCF-binding sites should exist between individual genes of a Hox cluster. This property is well documented in both vertebrates and Drosophila (10,28,40,43,55,56), suggesting that it existed in the ancestor of protostomes and deuterostomes. Second, owing to the stability of the proposed kernel, one should find signs of conservation at least at some CTCF-binding sites.…”
Section: Conservation Of Ctcf Sites In Vertebrate and Drosophila Hox mentioning
confidence: 95%
“…In D. melanogaster, CTCF confers insulator activity to the Fab-6 and Fab-8 chromatin boundaries within the Bithorax Hox complex (BX-C) (10,41). With the exception of Fab-7, all known and postulated boundaries within BX-C bind CTCF in vivo (28 transformations (31,42).…”
Section: Conservation Of Ctcf Sites In Vertebrate and Drosophila Hox mentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Furthermore, both context-dependent activity and ubiquitous global distribution are conserved throughout vertebrates and insects. [7][8][9][10][11][12][13] Recent studies of CTCF suggest that the mechanism of this multifunctional transcriptional regulation may involve higher order chromatin structure.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed an abundance of putative insulator elements bound by the enhancer-blocking protein CTCF in mammalian genomes, and predicted a similar number of binding sites in Tetraodon (Kim et al 2007;Xie et al 2007). Human CTCF is functionally conserved in Drosophila, where several other enhancer-blocking proteins also are known (Moon et al 2005). It will be interesting to see whether insulator elements are present at the borders of vertebrate and Drosophila GRBs.…”
Section: Responsiveness Of Genes To Long-range Enhancersmentioning
confidence: 99%